2018
DOI: 10.2355/isijinternational.isijint-2018-051
|View full text |Cite
|
Sign up to set email alerts
|

Strain Rate Sensitivity Behaviour of a Chrome-Nickel Austentic-Ferritic Stainless Steel and its Constitutive Modelling

Abstract: In the present investigation, the plastic flow curves and work softening behaviour of a dual phase Fe-Cr-Ni alloy during hot deformation (low to intermediate temperature range, 948 K (675°C) to 1 248 K (975°C)) along with concurrent microstructural development were investigated. The flow stress increased with the increase in strain rate and decreased with the increase in deformation temperature. The single peak characteristic appearing in all the flow curves indicated that dynamic recrystallization (DRX) was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The following is the calculation and fitting process of the general Arrhenius constitutive equation, which uses peak stress calculation. [ 35 ] Putting Equation (9) and (10) into Equation (8) and taking the natural logarithm obtains Equation (12) and (13). The relationship curves between for ln εfalse˙$\overset{.…”
Section: Resultsmentioning
confidence: 99%
“…The following is the calculation and fitting process of the general Arrhenius constitutive equation, which uses peak stress calculation. [ 35 ] Putting Equation (9) and (10) into Equation (8) and taking the natural logarithm obtains Equation (12) and (13). The relationship curves between for ln εfalse˙$\overset{.…”
Section: Resultsmentioning
confidence: 99%
“…Emami et al 6) investigated the behaviors of the austenite and ferrite phases in SAF2205 duplex stainless steel and reported that dissimilar behaviors occurred owing to the SFE. Kumar et al 7) reported that DRV is the prominent restoration process in ferrite with low values of the Zener-Hollomon parameters, whereas DRX is the prominent process in austenite with high values of the parameters.…”
Section: Flow Stress Of Duplex Stainless Steel By Inverse Analysis With Dynamic Recovery and Recrystallization Modelmentioning
confidence: 99%
“…( 5) and ( 6) can be expressed by the strain and strain rates, as shown in Eq. (7). Finally, applying Eqs.…”
Section: Constitutive Flow Stress Equations For the Duplex Stainless Steelmentioning
confidence: 99%
“…As an alternative, dual-phase steel can be economically produced by hot deformation method starting with an austenitic microstructure followed by quenching [9]. Compact slab production technology offers an economic way to produce a hot rolled strip with characteristics comparable to those of a cold rolled material [10]. It combines steel making, steel refining, and thin slab caster with direct hot rolling to reduce production cost [11].…”
Section: Introductionmentioning
confidence: 99%